Matter in Loop Quantum Gravity - Date, G.; Hossain, G.M. (Symmetry, Integrability and Geometry: Methods and Applications, 2012)
Loop quantum gravity, a non-perturbative and manifestly background free, quantum theory of gravity implies that at the kinematical level the spatial geometry is discrete in a specific sense. The spirit of background independence also requires a non-standard quantum representation of matter. While loop quantization of standard model fields has been proposed, detail study of its implications is not yet available. This review aims to survey the various efforts and results.